2011
DOI: 10.1126/scisignal.2001617
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kβ Plays a Critical Role in Neutrophil Activation by Immune Complexes

Abstract: Neutrophils are activated by immunoglobulin G (IgG)-containing immune complexes through receptors that recognize the Fc portion of IgG (FcγRs). Here, we used genetic and pharmacological approaches to define a selective role for the β isoform of phosphoinositide 3-kinase (PI3Kβ) in FcγR-dependent activation of mouse neutrophils by immune complexes of IgG and antigen immobilized on a plate surface. At low concentrations of immune complexes, loss of PI3Kβ alone substantially inhibited the production of reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 59 publications
4
143
1
1
Order By: Relevance
“…An alternative explanation is that an effective agonist or the priming process is necessary to produce tyrosine-phosphorylated proteins, which have been reported to augment the action of Gβγ on p110β (37,38). A recent study has shown that p110β plays a critical role in leukotriene B 4 (a GPCR agonist)-induced superoxide production by IgG-activated neutrophils (39). The fact may also be explained by the latter explanation indicating the interaction between GPCR and tyrosine kinase-coupled receptors.…”
Section: Discussionmentioning
confidence: 84%
“…An alternative explanation is that an effective agonist or the priming process is necessary to produce tyrosine-phosphorylated proteins, which have been reported to augment the action of Gβγ on p110β (37,38). A recent study has shown that p110β plays a critical role in leukotriene B 4 (a GPCR agonist)-induced superoxide production by IgG-activated neutrophils (39). The fact may also be explained by the latter explanation indicating the interaction between GPCR and tyrosine kinase-coupled receptors.…”
Section: Discussionmentioning
confidence: 84%
“…IPI-145 is much less active against PI3Ka and has a modest effect on PI3Kb. Although the role of PI3Kb is uncertain due to embryonic lethality in knockout mice, some data suggest that it can regulate neutrophil function (Kulkarni et al, 2011). Nevertheless, it is more likely that the pharmacologic activity observed in AA and CIA models is primarily due to an action on d and g isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, neutrophils from mice lacking PI3K␤ and expressing kinase-dead PI3K␦ D910A displayed a marked reduction in neutrophil ROS generation. The importance of PI3K␤ and its cooperation with PI3K␦ was further underlined by a study from the same group that demonstrated PI3K␤ plays an essential, nonredundant role in the efficient activation of mouse neutrophils by IgG-containing immune complexes (Kulkarni et al, 2011). Neutrophils detect these immune complexes through Fc receptors for IgG (Fc␥Rs).…”
Section: B Phosphoinositide 3-kinase ␤ and ␦ Coordinate The Respiratmentioning
confidence: 99%